Written spaces. The formats of Luis Pérez’s newspapers and loose leaf pages (1833) (Anclajes, 2017)
Based on contributions from historical reading, bibliographical material and analyses of Louis Marin’s visual representation, this paper addresses the formats of a group of printed texts published by the gaucho-esque writer Luis Peréz between 1830 and 1833, specifically a series of loose leaf pages and the two newspapers El Gaucho and La Gaucha. Its aim is to explore links between the material features of these works, the type of reader which the author attempted to attract, and the meaning and ideology of his texts.
Keywords: Luis Pérez; Argentinian literature; literary criticism; 19th century; Argentina